2006
DOI: 10.1207/s15548430jlr3804_2
|View full text |Cite
|
Sign up to set email alerts
|

Beginning Reading Materials: A National Survey of Primary Teachers' Reported Uses and Beliefs

Abstract: This study examined the opinions of more than 300 primary teachers. The first purpose of the study was to investigate the reported frequency with which teachers used various beginning reading materials (e.g., literature, basals, workbooks, predictable text, leveled text, decodable text, and vocabulary-controlled text). The second purpose of the study was to inspect how instructional purposes, state text policies, programs, grade levels, and freedom of choice influenced reported uses. The results suggested that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…Consequently, we selected “prototypes” to represent each category (Hiebert & Pearson, 2010), and, where series existed, texts were sampled from the range in the series. In reality, many early-grades texts fall into two or more of the category types (Mesmer, 2006). For example code-based texts are often “leveled.” However, for our purposes of ensuring wide representation of text types, each text was assigned to a single category.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Consequently, we selected “prototypes” to represent each category (Hiebert & Pearson, 2010), and, where series existed, texts were sampled from the range in the series. In reality, many early-grades texts fall into two or more of the category types (Mesmer, 2006). For example code-based texts are often “leveled.” However, for our purposes of ensuring wide representation of text types, each text was assigned to a single category.…”
Section: Methodsmentioning
confidence: 99%
“…Some commonly occurring early-grades texts, such as label books, do not fit well into the previous categories. The first four category labels are common terms used by educators and publishers (Mesmer, 2006).…”
Section: Textsmentioning
confidence: 99%
See 1 more Smart Citation
“…Research has identified that inconsistencies may exist between what teachers believe about appropriate literacy pedagogy and their actual practices in the classroom. Such inconsistencies may be due to a mismatch between personal beliefs and external factors, such as needing to produce evidence of meeting government compliance requirements (Foote et al, 2004;Mesmer, 2006), or due to policy pressures (Stipek & Byler, 1997). These factors may influence motivation for using commercial phonics programs.…”
mentioning
confidence: 99%
“…These surveys included questions about literacy instruction and resources. We generated original survey questions that reflected key content in the Essential Practices (MAISA ELTF, 2016) and adapted items from other surveys related to literacy instruction and/or similar literacy policies (e.g., Mesmer, 2006). To refine questions, we worked with external stakeholders and policymakers, including the Michigan Department of Education and the Michigan Association of Intermediate School Administrators (MAISA) General Education Leadership Network's (GELN) Early Literacy Task Force (ELTF).…”
Section: Methodsmentioning
confidence: 99%